The interplay between voluntary food intake, dietary carbohydrate-lipid ratio and nutrient metabolism in an amphibian, (Xenopus laevis) - Brenes Soto, Andrea (2018)
Digestion of food and metabolism of frogs are little studied at the moment, and such processes could be very particular in the case of amphibians, given their ectothermic and carnivorous nature which may lead them to use nutrients through specific biochemical pathways. In the present study, 24 adult Xenopus laevis (six replicates with two frogs per treatment) were randomly assigned to two diets with different carbohydrate:fat ratio (4.5:1 and 2.1:1), changing the dietary glucogenic and lipogenic proportions. Food intake (FI) per unit metabolic body weight (MBW) as well as macronutrient digestibility were calculated, and circulating blood acylcarnitines and amino acids measured, in order to evaluate the effect of the diet treatments. Results demonstrated that food intake regulated most of the changes in the parameters evaluated; significant differences were obtained in crude protein and fat digestibilities through the effect of FI/MBW (p<0.05), whereas diet treatment had a significant effect on the levels of malonyl-CoA. Food intake also significantly impacted malonyl, isovaleryl, hydroxyisovaleryl and long chain fatty acid concentrations; significant (p<0.05) interactions between those metabolites were detected owing to diet. The findings obtained suggest that food intake was the main factor controlling digestion and metabolism in X. laevis, with frogs preferring to utilise protein and fat as primary sources for energy production in the citric acid cycle, reflecting characteristics of a strict carnivore physiological model.